The Moral Economy of the Capitalist Crowd: Utopianism, the Reality of Society, and the Market as a Morally Instituted Process in Karl Polanyi’s The Great Transformation - Somers, Margaret R. (Humanity: An International Journal of Human Rights, Humanitarianism, and Development, 2020)
In an age of egregious inequality and rising authoritarian, many call for a new “moral economy” and turn to Karl Polanyi’s The Great Transformation for inspiration. Yet Polanyi’s great insight is that those who cannot reckon with the moral economy of “market justice”—the claim that market outcomes, however unequal, are morally just—fail to understand the power of capitalism. Justified by its original claim to rest on natural science, market justice laid the predicate for democracy as mortal threat. Polanyi reveals market justice as based not on natural law but on predistributive political power, and builds his democratic socialist vision on the “reality of society.”
Political Science
Keywords: market justice; moral economy